Economic Structure, Administrative Capacity, and Public Trust in Tax Performance: A Service-Centered Systematic Review across Income Groups, 2015–2025 - Haptari, Vissia Dewi; Sriyanto, Agus; Hamzah, Muhammad Zilal; Sofilda, Eleonora (Jurnal Manajemen Pelayanan Publik, 2026)
Cross-country variation in tax-to-GDP ratios reflects differences in economic structure, administrative capacity, and public trust under diverse institutional settings. This study provides a PRISMA-guided systematic review (2015–2025) to explain the determinants of tax performance across income groups. We identify 150 eligible studies and compile a core set of 90 for comparative synthesis, applying quality weights based on research design and methodological transparency. Higher-quality evidence links higher income per capita and stronger governance to higher tax ratios, while inflation and poorly managed resource rents weaken non-resource tax effort; digital tax administration (e-filing, e-invoicing, and risk-based analytics) is generally associated with higher compliance, but effects depend on baseline capacity, service design, and bureaucratic integrity. The review advances a service-centered framework integrating fiscal-contract and institutional-capacity perspectives into a “service–trust–revenue” loop and a “tax-capacity ladder”, with policy implications on reform sequencing: strengthening governance, modernizing administration, and progressively broadening the tax base through transparent communication and risk-based digital enforcement.